Effects of Different Types of Rubric-Based Feedback on Learning Outcomes - Sáiz-Manzanares, María Consuelo; Cuesta Segura, Isidoro Iván; Alegre Calderon, Jesús Manuel; Peñacoba Antona, Lorena (Frontiers in Education, 2017)
Nowadays in Higher Education, the teaching procedures that lead to better Learning Outcomes (LO) require continuous analysis. Rubrics such as teaching feedback procedures have demonstrated their effectiveness at heightening the reflection of university students on their own practice. The aims were: 1) to study the effects of different types of rubric-based feedback [from process-oriented feedback to traditional feedback] on LO and on student perceptions of subject matter knowledge (SPKI) in a comparison between students in engineering and students in the social sciences; 2) to analyze the relation between metacognitive skills and motivation with LO and SPKI; 3) to validate the results with structural equation modeling (SEM). The study comprised a total of 171 university students (n = 80 from the mechanical engineering degree and n = 91 from social sciences degree). A quasi-experimental design with a control group was used to test aim 1 and a descriptive correlational design to test aim 2. SEM was applied to validate the results (aim 3). Significant differences were found between both types of rubric-based feedback (process-oriented v. traditional) in relation to LO, though not in relation to SPKI. The effects of the degree type were noted in LO but no in SPKI. Likewise, a relation between SPKI and motivation skills was found in engineering students. Accordingly, the type of degree and the characteristics of the subject modules appear to be determining factors in successful learning, while SPKI is directly linked to motivation skills. The SEM results validated these conclusions.